The Semantic Role of Linguistic Context and Its Impact on Understanding the Holy Qur’an (The International Journal for Scientific Research, 2026)
This study examines the semantic-linguistic role of context and its impact on understanding Qur’anic vocabulary, starting from a central research question: to what extent does context contribute to determining the correct meaning of the Qur’anic text and guiding its multiple interpretations? The significance of this study lies in the fact that context constitutes a fundamental pillar of semantics, as Qur’anic expressions cannot be accurately understood in isolation from their linguistic, situational, and historical contexts.The research adopts a descriptive-analytical approach, drawing on the Arabic linguistic heritage of grammarians and rhetoricians, while also benefiting from the views of exegetes and linguists such as Sibawayh and Al-Khalil ibn Ahmad. In addition, it analyzes Qur’anic examples that demonstrate the role of context in shaping meaning. The study also addresses the concept of context in its two dimensions: textual context and situational context, highlighting the role of linguistic and extra-linguistic clues in determining meaning.The findings reveal that the Qur’anic word does not possess an independent meaning outside its context, and that the multiplicity of meanings in Qur’anic vocabulary is closely related to context, exegetical interpretations, and variations in Qur’anic readings. The study further confirms that context contributes to the transmission of words from their lexical meanings to technical or theological meanings, and that it plays a decisive role in understanding the rhetorical inimitability of the Qur’an. It also demonstrates that early Arab scholars were aware of the concept of context, even if they did not formulate it in its modern terminological sense.The study concludes that a proper understanding of the Holy Qur’an requires considering context in all its linguistic, historical, and social dimensions, and that neglecting it leads to flawed interpretation and misunderstanding of meanings, making context an indispensable tool in Qur’anic and linguistic studies.
Keywords: Semantics; Context; Qur’anic Vocabulary; Qur’anic Readings (Qirāʾāt); Exegesis (Tafsīr); Rhetorical Inimitability